A Systematic Approach to the Motivations for Earnings Management: A Literature Review - Callao, Susana; Jarne, Jose I.; Wroblewski, David (International Journal of Emerging Trends in Social Sciences, 2021)
Earnings management literature attempts to understand why managers manipulate earnings. Our paper presents a review of growing body of literature on motivations for the earnings manipulation. In consequence, our objective is to provide an ample classification of the reasons. A selection of leading papers was reviewed systematically from 1985 to early 2019 resulting in 383 articles. The results of the paper are important for both theoretical and empirical researches on the earnings management. For one side, we offer a theoretical discussion on the incentives and factors; on the other side, the paper aims to highlight recent progresses in the field. Screening, classifying and systematic review of earnings management literature do not only generate a structured overview of the work performed in this area during more than thirty years, but it also provides insights for further research. Our findings confirm that earnings management topic remains a fertile ground for academic research. Second, although there are many possible motives for managing earnings, the spotlight has been mainly on those incentives that are related to the stock market. Third, in terms of the factors and characteristics of the environment, the impact of institutional factors (investor protection, ownership concentration, legal enforcement) is especially accentuated by the authors. Finally, our research confirms that there are still many other opportunities to research. Therefore, in the last section we identify potential line of investigations.